Inhibitory Effect of Nutmeg (Myristica fragrans) Leaf Extract on Biofilm Formation by Methicillin-Resistant Staphylococcus aureus (MRSA) - Ramadhan, Fahri; Nugroho, Yusuf Eko; Faizal, Imam Agus (Asosiasi Institusi Pendidikan Tinggi Teknologi Laboratorium Medik Indonesia, 2025)
Background: Methicillin-resistant Staphylococcus aureus (MRSA) is an opportunistic pathogen with a strong capacity for biofilm formation, which enhances resistance to antibiotics. Although nutmeg (Myristica fragrans) seeds and mace have been extensively studied, research on nutmeg leaves is limited despite their content of flavonoids, tannins, saponins, and triterpenoids with antimicrobial potential. Objective: This study evaluated the antibiofilm activity of nutmeg leaf extract against MRSA biofilm formation in vitro. Materials and Methods: Biofilm assays were conducted using MRSA isolates. The optimal incubation time for biofilm formation was first determined, followed by treatment with nutmeg leaf extract. Results: MRSA formed optimal biofilms at 48 h (OD = 0.101 ± 0.012). Nutmeg leaf extract significantly reduced biofilm formation (OD = 0.083 ± 0.010) compared with the negative control (OD = 0.118 ± 0.009) and the positive control, tetracycline (OD = 0.096 ± 0.011) (p = 0.001). While the reduction was statistically significant, the difference from tetracycline was modest. Conclusion: Nutmeg leaf extract demonstrated significant antibiofilm activity against MRSA in vitro. These findings support its potential as a complementary natural agent for managing biofilm-associated infections, warranting further studies to isolate active compounds and assess synergistic effects with standard antibiotics.